Topical Ocular Administration of Progesterone Decreases Photoreceptor Cell Death in Retinal Degeneration Slow (rds) Mice - Adrián M. Alambiaga-Caravaca; Antolín Cantó; Vicent Rodilla; María Miranda; Alicia López-Castellano (MDPI AG, 2022)
Retinitis pigmentosa (RP) is an inherited eye disorder which triggers a cascade of retinal disorders leading to photoreceptor cell death and for which there is currently no effective treatment. The purpose of this research was to study whether ocular administration of a solution of progesterone (PG) in β-cyclodextrins (CD) could delay photoreceptor cell death and counteract the gliosis process in an animal model of RP (rds mice). The possible effect of PG reaching the contralateral eye through the circulatory system was also evaluated. Finally, this research discusses and evaluates the diffusion of the drug from possible topical formulations for ocular administration of PG. A group of rds mice received one drop of a solution of PG in CD every 12 h for 10 days to the left eye, while the right eye was left untreated. Another group of rds mice (control) received the drug vehicle (PBS) on the left eye and, again, the right eye was left untreated. Once the treatment was finished on postnatal day 21, the animals were euthanized and histological immunofluorescence studies (TUNEL, GFAP, and DAPI staining) were carried out. Our results showed that the administration of a solution of PG in CD (CD-PG) as drops significantly decreased cell death and inflammation in the retina of the PG-treated eyes of rds mice. No effect was seen in the contralateral eye from PG that may have entered systemic circulation. In conclusion, CD-PG applied topically as drops to the eye decreases photoreceptor cell death in the early stages of RP, delaying vision loss and decreasing gliosis.